Empowering teachers in item response theory analysis using R Studio in Manokwari - Achmad Rante Suparman; Murtihapsari Murtihapsari; Purwati Purwati (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang)
The training program on item response theory (IRT) analysis using R Studio for teachers in Manokwari aims to enhance their understanding of modern test theory and their ability to use R Studio as an analytical tool. Many teachers are unfamiliar with these concepts, so the training provides in-depth knowledge and practical applications to analyze test data and estimate student abilities. This interactive, practice-based training involved 30 teachers and included socialization, training, technology application, mentoring, and evaluation of R Studio in test item analysis. The results showed a significant improvement in teachers' knowledge and skills. Before the training, 90 percent of teachers were unfamiliar with R Studio, and 70 percent lacked understanding of IRT. After the training, 70 percent of teachers could use R Studio for student answer analysis, and 80 percent demonstrated a good grasp of modern test theory concepts. This improvement reflects the program's success in achieving its objectives and has the potential to enhance the quality of educational assessments in Manokwari. By utilizing IRT analysis more effectively, teachers can make better-informed decisions in the teaching and learning process, ultimately contributing to improved educational outcomes.